Frequency and clinicopathological characteristics of variants of primary focal segmental glomerulosclerosis in adults presenting with nephrotic syndrome - Shaheera Shakeel; Muhammed Mubarak; Javed I. Kazi; Nazrul Jafry; Ejaz Ahmed (Society of Diabetic Nephropathy Prevention, 2013)
Background: There is no information on the frequency and clinicopathological presentation of the variants of primary focal segmental glomerulosclerosis (FSGS) in adults presenting with idiopathic nephrotic syndrome (INS) in Pakistan. Objectives: The aim of this study was to determine the frequencies of different histologic variants of primary FSGS with INS at our center and to compare our findings with those published in literature. Patients and Methods: All consecutive adults (≥18 years) with INS, and diagnosis of FSGS on renal biopsies, were included. Their clinicopathological features at the time of presentation were retrieved and compared among the variants. Results: There were 120 (65.2%) males and 64 (34.8%) females. The mean age was 30.62±12.02 years. The mean 24-hr urinary protein excretion was 4.69±2.36 grams. Microscopic hematuria was found in 30 (16.3%) patients. The mean serum creatinine was 1.58±0.87 mg/dL. At presentation, 128 (69.6%) patients were normotensive, while 56 (30.4%) exhibited hypertension. FSGS, not otherwise specified (NOS) was the predominant variant, comprising 76.6% of all; collapsing variant comprised 12%, tip variant, 9.8%, perihilar, 1.1%, and cellular, 0.5%. The mean number of glomeruli involved by segmental scarring was 3.41±2.87 and there was significant difference among the variants (p= 0.001). Arteriolopathy was found in 23.4 % cases and fibrointimal thickening of arteries in 18.5%. Tubular atrophy and interstitial fibrosis (IF/TA) was noted in 93% of cases. There was no significant difference in vasculopathy and IF/TA among the variants. Conclusions: Collapsing variant was the second most common variant following NOS and these findings are different from other regional studies.